Metastatic Calcinosis Cutis Secondary to Selective Fibroblast Growth Factor Receptor Inhibitor: Rapid and Complete Regression after Blood Phosphate Normalization and Drug Withdrawal - Daniel Lopez-Castillo; Alvaro March-Rodriguez; Alejo Rodriguez-Vida; Ramon M. Pujol; Sonia Segura (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)